1979
DOI: 10.1002/ijc.2910240603
|View full text |Cite
|
Sign up to set email alerts
|

Glycophorin a as a cell surface marker of early erythroid differentiation in acute leukemia

Abstract: We show here that the leukemic blast cells from three patients of a total of 15 subsequently diagnosed as having acute leukemia express on their surface the major red cell sialoglycoprotein, glycophorin A (GP-A). This was demonstrated (1) by indirect immunofluorescence using rabbit anti GP-A anti-serum and (2) by immune precipitation of GP-A from surface radiolabelled leukemic cells. Since GP-A is exclusively present on erythroid cells and their precursors, these findings indicate that a higher proportion of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
4

Year Published

1981
1981
1990
1990

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(21 citation statements)
references
References 18 publications
1
16
4
Order By: Relevance
“…Normal morphologically distinguishable erythroid cells, similar to megaloblasts in pernicious anemia and AEL cells, were clearly positive, however. This is in contrast to the observations made by Anderson et a1 [3,4]. When studying the expression of GpA on leukemic blast cells with a rabbit anti-GpA antiserum, they found positive reactions in 3 of 15 cases [3] and later in 6 of 51 cases 141.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Normal morphologically distinguishable erythroid cells, similar to megaloblasts in pernicious anemia and AEL cells, were clearly positive, however. This is in contrast to the observations made by Anderson et a1 [3,4]. When studying the expression of GpA on leukemic blast cells with a rabbit anti-GpA antiserum, they found positive reactions in 3 of 15 cases [3] and later in 6 of 51 cases 141.…”
Section: Discussioncontrasting
confidence: 83%
“…It was therefore suggested [3] that GpA may provide a useful marker for the red cell lineage. The potential importance of such a marker has been further substantiated by the observation of Andersson et a1 that a large proportion of leukemic blast cells from 6 of 51 patients with acute leukemia reacted with a rabbit anti-GpA antiserum [4].…”
Section: Introductionmentioning
confidence: 99%
“…We have earlier reported that the malignant blasts in a significant proportion (610%) of undifferentiated acute leukemias carry surface structures that react with rabbit anti-GPA antiserum (41). Using monoclonal antibodies to GPA for the phenotyping of leukemic cells, only occasional reactivity is found (22,42).…”
Section: Discussionmentioning
confidence: 99%
“…Incubation with dimethyl sulfoxide (Me2SO) induces HL-60 to maturate into myelocytes and granulocytes (9) which have acquired functional properties characteristic of these cells (10). In contrast, the phorbol ester 12-0-tetradecanoylphorbol 13-acetate (TPA) induces differentiation ofHL-60 along the monocyte/macrophage pathway, with a concomitant increase in phagocytic capacity and adherence to plastic surfaces (11).…”
mentioning
confidence: 99%
“…Other cell lines of putative myeloid origin include K562 (12) which, by both immunological (13) and biochemical (14) criteria, is an erythroleukemic cell line, and the early myeloid cell line KG-1, which expresses the HLA-DR antigen (15,16). The relatively mature character of HL-60 is further evidenced by its lack of HLA-DR antigen normally present on myeloblasts (17).…”
mentioning
confidence: 99%